Pengaruh Online Customer Review, Content Marketing dan Brand Love Terhadap Keputusan Pembelian Produk Skintific Pada Platform Tiktok Shop - Fitri Oktafiani; Titin Hargyatni (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to determine and investigate the following: the direct influence of brand affection on the decision to buy skintific products on the TikTok Shop platform; the direct influence of content marketing on the decision to buy skintific products on the TikTok Shop platform; the direct influence of online customer reviews on the decision to buy skintific products on the TikTok Shop platform; and the combined influence of brand affection, content marketing, and online customer reviews on the decision to buy skintific products on the TikTok Shop platform. For this quantitative investigation, a sample of 70 respondents was chosen. The data was subjected to multiple linear regression analysis using IBM SPSS Statistics. This study's conclusions show that online customer reviews have a direct and significant influence on the purchase of skintific products on the TikTok Shop platform, brand affection has a significant influence on the purchase of skintific products on the TikTok Shop platform, content marketing has a significant influence on the purchase of skintific products on the TikTok Shop platform, and brand affection, content marketing, and online customer reviews all have an impact on the purchase of skintific products on the TikTok Shop platform at the same time.